Effect of Elevated Temperatures on Mortar with Naturally Occurring Volcanic Ash and Its Blend with Electric Arc Furnace Slag - Nauman Khurram; Kaffayatullah Khan; Muhammad Umair Saleem; Muhammad Nasir Amin; Usman Akmal (Advances in Materials Science and Engineering)
The mechanical behavior of basaltic volcanic ash (VA) and fly ash (FA) as a cement replacement under elevated temperatures is mainly investigated in the current study. For this, cement content has been partially replaced with and without the presence of electric arc furnace slag (S). Four distinct ranges of temperatures (200°C, 400°C, 600°C, and 800°C) were selected, and the modified mixes were subjected to these gradually elevated temperatures. Samples were cured and cooled by using air- and water-cooling techniques. Test results were established by examining the sample weights and compressive strength before and after the exposure of each temperature level. The pozzolanic potential of volcanic ash and fly ash samples was identified using the strength activity index. After analyzing the test results, it has been found that there is a significant effect on the compressive strength of mortar mixes at the early ages of its strength gain. However, at the later ages of curing, samples modified with volcanic and fly ash with the presence of electric arc furnace slag have shown a better performance than control mix in terms of strength and weight loss.